2009
DOI: 10.1016/j.visres.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Search superiority in autism within, but not outside the crowding regime

Abstract: Visual cognition of observers with autism spectrum disorder (ASD) seems to show an unbalance between the complementary functions of integration and segregation. This study uses visual search and crowding paradigms to probe the relative ability of children with autism, compared to normal developments children, to extract individual targets from cluttered backgrounds both within and outside the crowding regime. The data show that standard search follows the same pattern in the ASD and control groups with a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 38 publications
4
47
0
Order By: Relevance
“…Atypical low-level visual processing is further supported by the finding of altered occipital visual evoked potentials (VEPs) associated with sine-wave gratings of medium and high spatial frequency [76][77][78]. However, psychophysical measures of contrast sensitivity to several spatial frequencies showed that autistic individuals do not have different spatial frequency processing to NT individuals ( [79], see also [80,81]). In contrast to enhanced or intact sensitivity to luminance-defined (first-order) stimuli, autistic individuals show inferior sensitivity to texture-defined (second-order) stimuli, which involve mid-level visual processing [75,82].…”
Section: Visual Scene Analysis In Autismmentioning
confidence: 99%
“…Atypical low-level visual processing is further supported by the finding of altered occipital visual evoked potentials (VEPs) associated with sine-wave gratings of medium and high spatial frequency [76][77][78]. However, psychophysical measures of contrast sensitivity to several spatial frequencies showed that autistic individuals do not have different spatial frequency processing to NT individuals ( [79], see also [80,81]). In contrast to enhanced or intact sensitivity to luminance-defined (first-order) stimuli, autistic individuals show inferior sensitivity to texture-defined (second-order) stimuli, which involve mid-level visual processing [75,82].…”
Section: Visual Scene Analysis In Autismmentioning
confidence: 99%
“…However, as the age of participants in the present study resembles that of previous research O'Riordan 2004), and superior performance was actually found in experiment 2 (similar to Kemner et al 2007), this suggestion is not applicable to the present study. Second, Baldassi et al (2009) find no superiority for locating a deviant stimulus at the center of vision for a group of children with ASD compared to typically developing children. However, as the task in Baldassi et al (2009) measures sensitivity thresholds for briefly presented sets of stimuli, it is hard to compare their results to the present study.…”
Section: Discussionmentioning
confidence: 77%
“…Second, Baldassi et al (2009) find no superiority for locating a deviant stimulus at the center of vision for a group of children with ASD compared to typically developing children. However, as the task in Baldassi et al (2009) measures sensitivity thresholds for briefly presented sets of stimuli, it is hard to compare their results to the present study. The remaining option is that the difference in results between experiments 1 and 2 is due to differences in the visual search task itself.…”
Section: Discussionmentioning
confidence: 77%
“…As the age of the participants in the present study resembles that of previous research O'Riordan, 2004), and superior performance was actually observed in experiment 2 (similar to , this suggestion is not applicable to the present study. Second, Baldassi et al (2009) reported no superiority for locating a deviant stimulus at the center of vision for a group of children with ASD compared to typically developing children. However, as the task in Baldassi et al (2009) measured sensitivity thresholds for briefly presented sets of stimuli, it is hard to compare their results to the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Second, Baldassi et al (2009) reported no superiority for locating a deviant stimulus at the center of vision for a group of children with ASD compared to typically developing children. However, as the task in Baldassi et al (2009) measured sensitivity thresholds for briefly presented sets of stimuli, it is hard to compare their results to the present study. The remaining option is that the di↵erence in results between experiments 1 and 2 is due to di↵erences in the visual search task itself.…”
Section: Discussionmentioning
confidence: 94%